Diterpene Lactones from Andrographis paniculata and In Vitro Studies on α-Amylase and α-Glucosidase Inhibitory Properties - Rachmani, Eka Prasasti Nur; Rehana; Lestari, Puji; Fajriah, Sofa (Bogor Agricultural University, Indonesia, 2025)
Plants contain chemical compounds that have medicinal properties. Andrographis paniculata (bitter herb) is commonly used as a traditional medicine, including treating hyperglycemia. A. paniculata was known to contain major compounds, terpenoids, and flavonoids. The phytochemical investigation aimed to isolate and identify chemical compounds from the aerial part of the bitter herb and then evaluate the antihyperglycemic properties. A. paniculata was extracted using 96% ethanol. The extract was partitioned with three organic solvents successively to obtain the chloroform fraction, ethyl acetate fraction, and methanol fraction. Isolation was carried out on the ethyl acetate fraction using column chromatography with a silica stationary phase and an organic solvent mobile phase in various ratios. The isolate in the form of white powder was found in subfraction E8 with the mobile phase chloroform-ethyl acetate (1-2). The structure of the isolated compounds was characterized using spectroscopic methods, including 1D NMR (1H and 13C), 2D NMR (HSQC and HMBC), and LCMS. The isolated compounds were evaluated in vitro with α-amylase and α-glucosidase tests. The results of the data analysis indicated the identification of 14-deoxy-11,12-didehydroandrographolide and 14-deoxyandrographolide as the isolated compounds. The isolated compounds showed α-amylase inhibitory activity with an inhibitory concentration (IC50) of 167.31±4.92 μg/ml and α-glucosidase inhibitory activity with an IC50 of 267.10±6.72 μg/ml. The results of this study indicate that paniculata contains diterpene lactones, which are active in hyperglycemia therapy.